2013
DOI: 10.1038/oncsis.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 induces drug resistance in pancreatic cancer cells via upregulation of multidrug resistance genes

Abstract: MUC1 (CD227), a membrane tethered mucin glycoprotein, is overexpressed in >60% of human pancreatic cancers (PCs), and is associated with poor prognosis, enhanced metastasis and chemoresistance. The objective of this study was to delineate the mechanism by which MUC1 induces drug resistance in human (BxPC3 and Capan-1) and mouse (KCKO, KCM) PC cells. We report that PC cells that express high levels of MUC1 exhibit increased resistance to chemotherapeutic drugs (gemcitabine and etoposide) in comparison with cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
152
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 28 publications
5
152
0
Order By: Relevance
“…The expression of ATP-binding cassette transporters, which act as drug efflux pumps, is also associated with drug resistance in PDAC (36). The drug efflux pumps ABCB1 (MDR1/P-glycoprotein) and ABCC1 (MRP1) have been linked to the resistance of PDAC cells to gemcitabine (37,38). CYR61 has been previously reported to regulate expression of the drug efflux pump MDR1/P-glycoprotein in renal cell carcinoma (39), but it has not been studied in PDAC.…”
Section: Cyr61 Does Not Regulate Expression Of Other Gemcitabine Resimentioning
confidence: 99%
“…The expression of ATP-binding cassette transporters, which act as drug efflux pumps, is also associated with drug resistance in PDAC (36). The drug efflux pumps ABCB1 (MDR1/P-glycoprotein) and ABCC1 (MRP1) have been linked to the resistance of PDAC cells to gemcitabine (37,38). CYR61 has been previously reported to regulate expression of the drug efflux pump MDR1/P-glycoprotein in renal cell carcinoma (39), but it has not been studied in PDAC.…”
Section: Cyr61 Does Not Regulate Expression Of Other Gemcitabine Resimentioning
confidence: 99%
“…It is a highly aggressive cancer that is usually diagnosed at an advanced stage and has the worst prognosis of any malignancy, with a 7% 5-year survival rate due to high chemoresistance. This chemoresistance is due in part to altered expressions of mucins, which form a mesh that makes target sites inaccessible to drugs (2)(3)(4)(5)(6)(7)(8)(9). Clinical and preclinical studies have shown aberrant expression of mucins during pancreatic cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…The mucins may prevent drugs from accessing their sites of action. The expression of several mucins, including MUC1, MUC4, MUC5AC, and MUC16, is highly upregulated in pancreatic ductal adenocarcinoma (PDAC), pancreatic intraepithelial neoplasia (PanIN), intrapapillary mucinous neoplasms, and mucinous cystic neoplasms from patients with pancreatic cancer (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The extent to which the dense mucin mesh influences the antiproliferative activity of 5-fluorouracil (5-FU) was investigated using human pancreatic cancer cells (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Mucin 1 protein has been implicated in various aspects of tumor development, including angiogenesis (7), proliferation (8), migration (9), survival (10) and metastasis (11). Accumulating evidence indicates a causal association between MUC1 expression and chemoresistance of tumor cells (12,13). For instance, Nath et al (12) reported that MUC1 contributes to drug resistance in pancreatic cancer cells through upregulation of multidrug resistance genes, including ATP binding cassette subfamily C member (ABCC)1, ABCC3, ABCC5 and ABCB1.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates a causal association between MUC1 expression and chemoresistance of tumor cells (12,13). For instance, Nath et al (12) reported that MUC1 contributes to drug resistance in pancreatic cancer cells through upregulation of multidrug resistance genes, including ATP binding cassette subfamily C member (ABCC)1, ABCC3, ABCC5 and ABCB1. Overexpression of the oncogenic MUC1-C subunit has been identified to confer tamoxifen resistance in MCF-7 breast cancer cells (13).…”
Section: Introductionmentioning
confidence: 99%